Classification of Iraqi governorates by using cluster analysis for 2016 - Ashoor, Wafaa Abdul Samed (Journal of natural sciences, life and applied sciences, 2019)
The development of human societies is measured by the level of success achieved in health because of its direct link to human life. If any society can improve the health of its citizen, it will achieve similar success in other areas of life. If it fails in this aspect, it will fail in other aspects. So this important subject had to be discussed. This study aimed to know the difference between the Iraqi governorates in terms of the level of health indicators provided to the citizen, in addition to determining any of the indicators that contributed significantly to this difference and disparity between the provinces. Data were obtained from the Annual Statistical Abstract of 2017 issued by the Central Statistical Organization. The study included (13) governorates, except for the northern governorates, Mosul and Anbar because data is not available for these governorates and (25) variables representing health indicators. The cluster analysis method was used in the hierarchical and non-hierarchical way. The researcher concluded Baghdad is the best in providing health services to citizens, where the distance between them and other the governorates ranged from (3.875) to (4.841). and Najaf and Qadissiyah are close in providing these services to the citizen, Where the distance between them (0.411). And that the governorates clustered in three clusters, the first included (Kerkok, Diyala, Babylonl, Karbala, Wasit, Saladyn, Najaf, Qadisya, Muthanna, Thi Qar, Mysan) of and the second included Basra only and the third included Baghdad only.